Building loyalty in e-commerce: Towards a multidimensional trust-based framework for the case of China. Issue 4 (6th September 2016) - Xiao, Lin; Guo, Zixiu; D'Ambra, John; Fu, Bin
Abstract : Purpose: Although recent years have shown increasing popularity of e-commerce worldwide, there is still a lack of studies comprehensively exploring trust issue in e-commerce. Based on trust transfer theory and signaling theory, the purpose of this paper is to present an integrated research model to test the relationships between trust dimensions and e-loyalty, interactions among trust dimensions, as well as antecedents of different trust dimensions. Design/methodology/approach: Data were collected through a web-based survey in Chinese markets and structural equation modeling with partial least squares was used to analyze the data. Findings: The results identified that three trust dimensions all have significant impacts on e-loyalty, and relationships existed in different trust dimensions. Moreover, information quality and security protection are important factors determining institutional trust while store reputation is the most salient factor determining interpersonal trust. Originality/value: This research contributes to the body of knowledge on trust by exploring the nature of trust with a multidimensional scale. Another theoretical contribution is the provision of a comprehensive understanding of the trust antecedents in e-commerce. Furthermore, this research benefits the companies doing e-businesses by allowing them to better understand how to improve consumers' trust in the online environment and thus to retain and attract more loyal customers and succeed in online businesses.